PENGARUH TEKNOLOGI BLOKCHAIN TERHADAP EFISIENSI DAN KEAMANAN TRANSAKSI KEUANGAN: STUDI KASUS PADA INDUSTRI PERBANKAN DI INDONESIA - Erari, Anita; Hartono, Pierdijono; Surahman, Bambang; Mahdi, Mahdi; Kraugusteeliana, Kraugusteeliana (JURNAL ILMIAH EDUNOMIKA, 2024)
This Research aims to see the influence of bloking technology on the efficiency and security of financial transaction, with a case study in the banking industry in Indonesia. The method in this research uses a combination approach, including analytical and descriptive approaches. The result of this research are that the use of this technology provides significant benefits in terms of safety and operational efficiency. This blokchain technology can increase transaction security and reduce the risk of fraud, besides that it can strengthen data integrity so that transactions are more efficient. This blokchain technology can increase transaction security and increase the trust of customers and banking authorities.